1986
DOI: 10.1107/s0021889886089823
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of optical activity in crystal structures

Abstract: Close examination of published measurements of absolute configuration in inorganic crystals has revealed many mistakes, and only a small number of published correlations between optical rotation and chirality of crystal structure can be trusted. The sense of rotation of light is here traced to the hand of specific helices of atoms, provided that the latter are correctly chosen. Four principles are given for choosing the helices. The crystals described are: low-quartz, ~-A1PO4, ct-HgS, Ca2Sr(CzHsCOO)6, BitzSiO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
129
1
2

Year Published

1987
1987
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 29 publications
5
129
1
2
Order By: Relevance
“…A number of approximations have had to be made in this example, but, even so, the results of our computations are most encouraging. As with the examples used by Glazer & Stadnicka (1986) and by Devarajan & Glazer (1986), it is seen that the major influence on the optical properties comes from the structural arrangement of the atoms in the crystal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of approximations have had to be made in this example, but, even so, the results of our computations are most encouraging. As with the examples used by Glazer & Stadnicka (1986) and by Devarajan & Glazer (1986), it is seen that the major influence on the optical properties comes from the structural arrangement of the atoms in the crystal.…”
Section: Discussionmentioning
confidence: 99%
“…Following Glazer & Stadnicka (1986) we first choose the most polarizable atoms, which, in this structure, are the O atoms. Because the Ni-O bonds are weaker than the S-O bonds (as shown by the relative bond distances), O(1), 0(2) and 0(3) will have larger electronic polarizabilities than 0(4) and O(5), and so they should contribute more strongly towards the optical activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using this relation and the conclusions of LFC, they found a correlation between the absolute structure and the optical chirality. From a structural approach to optical activity, Glazer & Stadnicka (1986) (GS) showed that the determination of the structural enantiomorph by LFC seemed to be in error. Stadnicka, Glazer & Moxon (1985) (SGM) redetermined the absolute configuration of LilO3 and showed that the correlation between the absolute configuration and the optical chirality found by LFC and SALKA was incorrect.…”
Section: Introductionmentioning
confidence: 99%